Diabetes and COVID-19: A Review - Baidya, Arjun; Singh, Santosh Kumar; Bajaj, Sarita; Zargar, Abdul Hamid; Singh, Parminder; Das, Sambit; Shankar, Anand (Journal of the ASEAN Federation of Endocrine Societies, 2020)
Coronavirus Disease 2019 (COVID-19) is an emerging disease and since its first identification in Wuhan, China, in December 2019, there has been a rapid increase in cases and deaths across the world. COVID-19 has been shown to have an immense impact in infected persons with diabetes, worsening their outcome, especially in elderly, smokers, obese, those having CVD, CKD, poor glycemic control and long duration of diabetes. In this review we summarize the current understanding of `the impact of COVID-19 on diabetes and discusses the pathophysiological mechanisms and management of diabetes and its complication in this scenario.